Evolution and characterization of olive genetic resources in Palmyra / Central Syria - Ghada Kattmah; Jwad Enad Mahd Al-kalaby; Mostafa Murshed Al-Rasheed; Anwar Al-Ibrahem (Kufa Journal for Agricultural Sciences)
haracterize the olive cultivars to the application adopted by the International Olive Council, and to study the most important technological characterization (size of fruits and stones, their weight and pulp / stone ratio).